Porous carbon material and method for producing the same
Patent Information
- Application Number
- CN202610929874.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,上述方法在孔结构调控方面普遍存在介孔结构难以精准调控、碳骨架容易坍塌、介孔占比偏低的技术问题
[0004] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention provides a porous carbon material and its preparation method, which introduces oxygen-containing functional groups such as carbonyl and ester groups into the precursor framework using an oxidant, significantly increasing the proportion of mesopores in the overall pore structure of the porous carbon material.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional carbon materials technology, specifically to porous carbon materials and their preparation methods. Background Technology
[0002] Precise control of pore structure has always been a key research focus for porous carbon materials. Among related technologies, the control of pore structure in porous carbon is mainly divided into two types: physical activation and chemical activation. Physical activation typically uses carbon dioxide as an etching medium to create pores by etching the carbon matrix framework, thereby achieving precise control of the pore structure. Chemical activation, on the other hand, often uses alkaline activators to etch the carbon material itself to complete the pore construction.
[0003] However, the aforementioned methods generally suffer from technical problems in pore structure control, including difficulty in precisely controlling the mesoporous structure, easy collapse of the carbon framework, and low mesopore ratio. Therefore, there is an urgent need for a method to prepare porous carbon materials that can efficiently construct and precisely control the mesoporous structure, increase the mesopore ratio, and avoid carbon framework collapse. Summary of the Invention
[0004] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention provides a porous carbon material and its preparation method, which introduces oxygen-containing functional groups such as carbonyl and ester groups into the precursor framework using an oxidant, significantly increasing the proportion of mesopores in the overall pore structure of the porous carbon material.
[0005] The first aspect of the present invention provides a method for preparing a porous carbon material, comprising: Phenolic monomers, aldehyde monomers, catalysts, surfactants, oxidants and water are mixed and the resulting raw material mixture is subjected to a first reaction to obtain a functionalized phenolic resin precursor. The functionalized phenolic resin precursor is mixed with an activator to carry out a second reaction, thereby obtaining a porous carbon intermediate. The porous carbon intermediate was acid-washed with acid to obtain a porous carbon material.
[0006] Therefore, by introducing an oxidant during the synthesis of phenolic resin and introducing oxygen-containing functional groups such as carbonyl and ester groups into the framework, the bending and reconstruction of these functional groups during the subsequent high-temperature carbonization process can induce the merging and annihilation of micropores, thereby significantly increasing the proportion of mesopores in the overall pore structure during activation. Compared with the traditional method of controlling the mesopore ratio by changing the type and amount of activator, this invention starts from the molecular design source of carbon precursors and introduces an oxidant in situ for control during the synthesis stage. This changes the traditional "etching-based" pore-forming approach, effectively increasing the mesopore ratio while avoiding the collapse of the carbon framework, significantly improving the stability and integrity of the carbon material structure. It provides a new route for preparing high-mesoporous porous carbon materials under non-template methods and non-strong etching conditions, which is of great value for the application of porous carbon in supercapacitors, catalyst supports, and other fields.
[0007] According to an embodiment of the present invention, the method for preparing the above-mentioned porous carbon material may further include at least one of the following additional technical features: In some embodiments, the preparation method includes at least one of the following conditions: The phenolic monomers include at least one of hydroquinone, catechol, resorcinol, and phenol; The aldehyde monomers include at least one of formaldehyde, furfural, vanillin, and acetaldehyde; The catalyst includes at least one of ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, diethylamine, dimethylethanolamine, ethylenediamine, and pyridine. The surfactant includes at least one of hexadecyltrimethylammonium bromide (CTAB), polyethylene glycol, and polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer; The oxidant includes at least one of sodium perborate, potassium ferrate, and ammonium persulfate. The functional group includes at least one of carbonyl and ester groups.
[0008] In some embodiments, the preparation method includes at least one of the following conditions: The mass ratio of the phenolic monomer, aldehyde monomer, catalyst, and surfactant is 1:(1.2~2.5):(0.06~0.1):(0.01~0.5). The mass ratio of the phenolic monomer to the oxidant is 1:(0.01~0.1). The amount of water used is 5% to 20% of the total mass of the solid raw materials in the raw material mixture; The temperature of the first reaction is 70℃~100℃, and the time is 2h~15h.
[0009] In some embodiments, prior to the second reaction, the preparation method further includes drying the functionalized phenolic resin precursor; preferably, the drying temperature is 70°C to 100°C.
[0010] In some embodiments, the preparation method includes at least one of the following conditions: The activator includes at least one of KOH and NaOH; The mass ratio of the functionalized phenolic resin precursor to the activator is 1:(1.2~2.5). The second reaction is carried out at a temperature of 800℃~1300℃ for a time of 2h~15h; The atmosphere for the second reaction is an inert atmosphere; preferably, the inert atmosphere includes at least one of nitrogen or argon.
[0011] In some embodiments, the preparation method includes at least one of the following conditions: The acid solution includes at least one of hydrochloric acid, sulfuric acid, and nitric acid; The mass ratio of the acid solution to the porous carbon intermediate is 1:(0.5~1.5).
[0012] In some embodiments, after pickling, the preparation method further includes post-treatment of the pickled product; preferably, the post-treatment includes: dispersing the pickled product in water, washing, and drying.
[0013] In some embodiments, the preparation method includes at least one of the following conditions: The dispersion period is 1 to 2 days; The washing process includes vacuum filtration washing; The washing is performed 3 to 5 times; The drying includes vacuum drying; The drying temperature is 70℃~100℃.
[0014] A second aspect of the present invention provides a porous carbon material prepared by the aforementioned preparation method. Thus, the porous carbon material possesses all the features and advantages of the aforementioned preparation method, which will not be repeated here.
[0015] In some embodiments, the mesopore content of the porous carbon material is 18% to 30%.
[0016] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0017] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0018] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0019] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0020] In this document, the terms “comprising” or “including” are open-ended expressions, meaning that they include the contents specified in this invention, but do not exclude other aspects.
[0021] In this document, the terms “optionally,” “optionally,” or “optionally” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur.
[0022] Unless otherwise specified, the term "parts" in this document refers to parts by mass. That is, the proportions of each component are calculated based on mass, and those skilled in the art will understand that this can be scaled up or down proportionally as needed in practice.
[0023] In related technologies, the pore structure control of porous carbon mainly relies on methods such as direct carbonization, activation, and template methods. However, the inventors found that the activation method often results in a wide pore size distribution and a low specific surface area (typically <1500 μm). 2 / g); While chemical methods can increase specific surface area, they can easily lead to problems such as excessive micropore ratio and carbon skeleton collapse; while template methods can achieve ordered arrangement of mesopores, they have problems such as complex template agent removal process, high cost, and easy damage to pore walls.
[0024] It is evident that related technologies often struggle to efficiently construct and precisely control mesoporous structures while preventing the collapse of the carbon framework, resulting in technical problems such as difficulty in precisely controlling the mesoporous structure and a low proportion of mesopores.
[0025] Based on the above research, the inventors developed a new method for preparing porous carbon materials. By using an oxidant to introduce oxygen-containing functional groups such as carbonyl and ester groups into the precursor framework, the proportion of mesopores in the overall pore structure of porous carbon materials is significantly increased.
[0026] The first aspect of the present invention provides a method for preparing a porous carbon material, comprising: Phenolic monomers, aldehyde monomers, catalysts, surfactants, oxidants and water are mixed and the resulting raw material mixture is subjected to a first reaction to obtain a functionalized phenolic resin precursor. The functionalized phenolic resin precursor is mixed with an activator to carry out a second reaction, thereby obtaining a porous carbon intermediate. The porous carbon intermediate was acid-washed with acid to obtain a porous carbon material.
[0027] Therefore, by introducing an oxidant during the synthesis of phenolic resin and introducing oxygen-containing functional groups such as carbonyl and ester groups into the framework, the bending and reconstruction of these functional groups during the subsequent high-temperature carbonization process can induce the merging and annihilation of micropores, thereby significantly increasing the proportion of mesopores in the overall pore structure during activation. Compared with the traditional method of controlling the mesopore ratio by changing the type and amount of activator, this invention starts from the molecular design source of carbon precursors and introduces an oxidant in situ for control during the synthesis stage. This changes the traditional "etching-based" pore-forming approach, effectively increasing the mesopore ratio while avoiding the collapse of the carbon framework, significantly improving the stability and integrity of the carbon material structure. It provides a new route for preparing high-mesoporous porous carbon materials under non-template methods and non-strong etching conditions, which is of great value for the application of porous carbon in supercapacitors, catalyst supports, and other fields.
[0028] In some embodiments, the phenolic monomer includes at least one of hydroquinone, catechol, resorcinol, and phenol.
[0029] In some embodiments, the aldehyde monomer includes at least one of formaldehyde, furfural, vanillin, and acetaldehyde.
[0030] In some embodiments, the catalyst includes at least one of ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, diethylamine, dimethylethanolamine, ethylenediamine, and pyridine.
[0031] In some embodiments, the surfactant includes at least one of cetyltrimethylammonium bromide (CTAB), polyethylene glycol, and polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer.
[0032] In some embodiments, the oxidant includes at least one of sodium perborate, potassium ferrate, and ammonium persulfate. This allows for the introduction of oxygen-containing functional groups such as carbonyl and ester groups into the framework through oxidation, significantly increasing the proportion of mesopores in the overall pore structure of porous carbon materials and preventing the collapse of the carbon framework.
[0033] In some embodiments, the functional group includes at least one of carbonyl and ester groups.
[0034] In some embodiments, the mass ratio of the phenolic monomer, aldehyde monomer, catalyst, and surfactant is 1:(1.2~2.5):(0.06~0.1):(0.01~0.5); specifically, it can be 1:1.2:0.06:0.01, 1:1.5:0.07:0.05, 1:1.8:0.08:0.1, 1:2.0:0.09:0.2, 1:2.2:0.09:0.3, 1:2.5:0.10:0.5, etc. This promotes the full progress of the first reaction while maintaining the stability of the suspension system, which is beneficial for obtaining a resin precursor with uniform particle size and uniform functional group distribution.
[0035] In some embodiments, the mass ratio of the phenolic monomer to the oxidant is 1:(0.01~0.1); specifically, it can be 1:0.01, 1:0.02, 1:0.04, 1:0.06, 1:0.08, 1:0.10, etc. This allows the phenolic resin precursor to be moderately oxidized, introducing appropriate amounts of oxygen-containing functional groups such as carbonyl and ester groups without disrupting the overall polymerization process. This is beneficial for increasing the proportion of mesopores in the overall pore structure of porous carbon materials and preventing the collapse of the carbon skeleton. If the oxidant ratio is too low, insufficient oxidation of functional groups may occur, weakening the regulatory effect on the pore structure during subsequent carbonization; if the oxidant ratio is too high, over-oxidation may occur, easily damaging reactivity, interfering with conventional condensation reactions, and generating excessive small-molecule byproducts.
[0036] In some embodiments, the amount of water used is 5% to 20% of the total mass of the solid raw materials in the raw material mixture; specifically, it can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc. This helps to control viscosity, improve monomer dispersion, and promote the stable progress of suspension polymerization. If the amount of water is too small, the viscosity of the system may be too high, leading to difficulties in stirring, poor heat dissipation, and even local overpolymerization; if the amount of water is too large, it may dilute the concentration of reactants, prolong the polymerization time, and increase the energy consumption for subsequent drying.
[0037] It should be noted that, in this invention, the total mass of the solid raw materials refers to the sum of the masses of each raw material that exists in solid form and participates in the reaction at room temperature (25°C). For example, the total mass of the solid raw materials in the raw material mixture is the sum of the masses of each raw material in the raw material mixture that exists in solid form at 25°C.
[0038] In some embodiments, the temperature of the first reaction is 70℃~100℃, and the time is 2h~15h; specifically, the temperature of the first reaction can be 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, etc., and the time can be 2h, 4h, 6h, 8h, 10h, 12h, 15h, etc. This facilitates a stable condensation reaction, promotes full cross-linking of phenolic monomers and aldehyde monomers, and allows the oxidation reaction to occur moderately, resulting in a functionalized phenolic resin precursor with a uniform structure and suitable functional group distribution. If the temperature of the first reaction is too low, it may reduce the polymerization rate and the degree of oxidation; if the temperature is too high, the reaction may become too vigorous, potentially leading to local overheating or an increase in side reactions, affecting product consistency. If the time of the first reaction is too short, it may reduce the degree of polymerization and the molecular weight of the precursor; if the time is too long, it may lead to over-cross-linking, reducing the specific surface area and mesoporosity of the porous carbon material.
[0039] In some embodiments, prior to the second reaction, the preparation method further includes drying the functionalized phenolic resin precursor; preferably, the drying temperature is 70°C to 100°C; specifically, it can be 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc. This helps to remove moisture and residual solvent while preventing irreversible shrinkage of the precursor structure. If the drying temperature is too low, incomplete drying may occur, and residual solvent may remain in the precursor, affecting the structural uniformity and mesopore number of the porous carbon material; if the drying temperature is too high, the precursor surface may harden prematurely or undergo localized excessive cross-linking, leading to internal pore collapse and reducing the porosity of the porous carbon material.
[0040] In some embodiments, the activator includes at least one of KOH and NaOH.
[0041] In some embodiments, the mass ratio of the functionalized phenolic resin precursor to the activator is 1:(1.2~2.5); specifically, it can be 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2.0, 1:2.2, 1:2.5, etc. This facilitates moderate etching of the carbon skeleton during activation, inducing the full development of the mesoporous structure, while avoiding excessive etching that could damage the integrity of the carbon skeleton. If the activator ratio is too low, it may be difficult to effectively create pores, resulting in a low specific surface area and insufficient mesoporous proportion in the product; if the activator ratio is too high, it can easily lead to excessive etching of the carbon skeleton, potentially causing pore wall collapse or an abnormally high micropore proportion, thereby reducing the structural stability of porous carbon.
[0042] In some embodiments, the temperature of the second reaction is 800℃~1300℃, and the time is 2h~15h; specifically, the temperature of the second reaction can be 800℃, 850℃, 900℃, 950℃, 1000℃, 1100℃, 1200℃, 1300℃, etc., and the time can be 2h, 4h, 6h, 8h, 10h, 12h, 15h, etc. This facilitates the full decomposition of oxygen-containing functional groups in the precursor, guiding the bending and reconstruction of carbon sheets, thereby promoting the effective construction of mesoporous structures. If the temperature of the second reaction is too low, the reaction rate may decrease, leading to insufficient mesoporous development; if the temperature is too high, it may easily lead to excessive graphitization of the carbon skeleton, potentially causing pore shrinkage or even collapse, reducing the proportion of mesopores. If the time of the second reaction is too short, the pore structure may be dominated by micropores, with a low proportion of mesopores; if the time is too long, it may cause the mesopores to further expand into micron-sized voids or cause excessive etching of the skeleton, thus reducing the specific surface area and structural strength of the porous carbon material.
[0043] In some embodiments, the atmosphere of the second reaction is an inert atmosphere; preferably, the inert atmosphere includes at least one of nitrogen or argon.
[0044] In some embodiments, the acid solution includes at least one of hydrochloric acid, sulfuric acid, and nitric acid.
[0045] In some embodiments, the concentration of the acid solution is 1 wt% to 10 wt%; specifically, it can be 1 wt%, 3 wt%, 5 wt%, 7 wt%, 8 wt%, 10 wt%, etc. This helps to effectively remove template agents or impurities while reducing chemical corrosion of the carbon framework and maintaining the integrity of the porous carbon material's pore structure. If the acid concentration is too low, it may be difficult to fully remove residual activators or impurities inside the pores, leading to partial pore blockage and hindering product pore development; if the acid concentration is too high, it can easily cause excessive etching of the carbon framework, reducing the structural stability and specific surface area of the porous carbon.
[0046] In some embodiments, the mass ratio of the acid solution to the porous carbon intermediate is 1:(0.5~1.5); specifically, it can be 1:0.5, 1:0.7, 1:0.9, 1:1.0, 1:1.1, 1:1.3, 1:1.5, etc. This allows the acid solution to fully wet the porous carbon intermediate, which is beneficial for removing residual template agents or impurities, while avoiding damage to the porous carbon framework structure from excessive acid washing. If the amount of acid solution is too small, residual impurities may clog some pores, reducing the specific surface area and pore volume of the porous carbon; if the amount of acid solution is too large, it may not only corrode the carbon framework but also increase the subsequent washing and purification processes and costs.
[0047] In some embodiments, after pickling, the preparation method further includes post-treatment of the pickled product; preferably, the post-treatment includes: dispersing the pickled product in water, washing, and drying.
[0048] In some embodiments, the dispersion time is 1 to 2 days; specifically, it can be 1.0 days, 1.2 days, 1.4 days, 1.6 days, 1.8 days, 2.0 days, etc. This facilitates the dissolution of residual acid and soluble impurities, improving its performance in adsorption, catalysis, or electrochemical energy storage. If the dispersion time is too short, it may reduce the dissolution rate of residual acid or impurities inside the pores, easily causing pore blockage or local acid residue after drying, affecting the purity of porous carbon; if the dispersion time is too long, it may reduce the mechanical strength of the carbon skeleton.
[0049] In some embodiments, the washing includes vacuum filtration washing.
[0050] In some embodiments, the washing is performed 3 to 5 times, specifically 3, 4, or 5 times. This helps to thoroughly remove residual acid and soluble impurities from the porous carbon intermediate, thereby improving the purity of the porous carbon material.
[0051] In some embodiments, the drying includes vacuum drying.
[0052] In some embodiments, the drying temperature is 70℃~100℃; specifically, it can be 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, etc. This helps to avoid excessive shrinkage of the carbon skeleton and improve the integrity of the pore structure of the porous carbon material. If the drying temperature is too low, residual solvent is easily retained inside the pores, reducing the specific surface area and pore volume of the product; if the drying temperature is too high, irreversible shrinkage or local sintering can easily occur on the porous carbon surface, potentially leading to pore structure collapse and reducing the porosity of the material.
[0053] A second aspect of the present invention provides a porous carbon material prepared by the aforementioned preparation method. Thus, the porous carbon material possesses all the features and advantages of the aforementioned preparation method, which will not be repeated here.
[0054] In some embodiments, the mesopore content of the porous carbon material is 18% to 30%; specifically, it can be 18%, 20%, 22%, 24%, 26%, 28%, 30%, etc. This allows mesopores to dominate the overall pore structure while maintaining a sufficient specific surface area, thereby improving the overall performance of porous carbon in adsorption, mass transfer, and ion diffusion. If the mesopore content is too low, the micropore ratio will be too high, which may make it difficult for large molecules to enter the pores, limiting its application in loading or energy storage fields. If the mesopore content is too high, it may be accompanied by a significant reduction in micropore content, resulting in a corresponding decrease in specific surface area, which is not conducive to fully utilizing the adsorption capacity of porous carbon.
[0055] It should be noted that, in this invention, the term "mesopore ratio" refers to the percentage of mesopore volume in a material relative to the total pore volume (micropores + mesopores + macropores); the mesopore ratio is calculated using the following formula: Mesopore percentage = mesopore volume ÷ total pore volume × 100%.
[0056] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0057] Example 1 Add 50 parts hydroquinone, 80 parts furfural, 3 parts ammonia solution (25% by mass), and 1 part sodium perborate to a three-necked flask. Separately, dissolve 1.5 parts polyethylene glycol in 20 parts deionized water, stirring until completely dissolved to form a transparent aqueous solution, and then add this solution to the flask. Introduce the above system at 5 °C. min -1 The temperature was raised to 80 °C in a water bath at a controlled heating rate, and then stirred at 80 °C for 10 h to carry out the first reaction, obtaining a functionalized phenolic resin precursor. The obtained precursor and activator KOH were mixed evenly at a mass ratio of 1:1 and placed in a tube furnace for activation at 800 °C for 4 h to carry out the second reaction, obtaining a porous carbon intermediate. The intermediate was then acid-washed with 5 wt% dilute hydrochloric acid (the mass ratio of intermediate to dilute hydrochloric acid was 1:0.5) for 24 h, followed by washing three times with anhydrous ethanol and drying at 80 °C for 18 h to finally obtain the porous carbon material.
[0058] Example 2 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the time for the first reaction in this embodiment is 8 hours.
[0059] Example 3 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that the time for the first reaction in this embodiment is 6 hours.
[0060] Comparative Example 1 This comparative example is based on Example 1, and the only difference from Example 1 is that sodium perborate was not added in this comparative example.
[0061] Comparative Example 2 This comparative example is based on Example 2, and the only difference from Example 2 is that sodium perborate was not added in this comparative example.
[0062] Comparative Example 3 This comparative example is based on Example 3, and the only difference from Example 3 is that sodium perborate was not added in this comparative example.
[0063] Performance testing The properties of the porous carbon materials prepared in the above embodiments and comparative examples were tested according to the following methods, and the results are recorded in Table 1.
[0064] 1. Oxygen Content and Ratio of Carbonyl and Ester Functional Groups: The chemical composition of the porous carbon material surface was analyzed using X-ray photoelectron spectroscopy (XPS). The atomic percentage of oxygen on the surface was obtained by full-spectrum scanning. Further peak fitting of the C1s high-resolution spectrum was performed to obtain the peak areas of carbonyl (C=O) and ester (OC=O) groups, as well as the total C1s peak area. The ratio of carbonyl and ester functional groups was calculated using the following formula: The ratio of carbonyl and ester functional groups = (carbonyl peak area + ester peak area) ÷ total C1s peak area × 100%; 2. Mesopore Ratio: The pore structure parameters of the porous carbon material were tested using a specific surface area and pore size analyzer. The cumulative pore volume of the porous carbon was calculated using nonlocal density functional theory (NLDFT) to obtain the mesopore volume and total pore volume, and the mesopore ratio was calculated according to the following formula: Mesopore percentage = mesopore volume ÷ total pore volume × 100%.
[0065] Table 1 Performance test results of the porous carbon materials prepared in the above embodiments and comparative examples
[0066] As shown in Table 1, the oxygen content, carbonyl and ester functional group ratios, and mesopore ratio of Examples 1-3 are all higher than those of Comparative Examples 1-3, indicating that the present invention can introduce oxygen-containing functional groups such as carbonyl and ester groups into the phenolic resin prepolymer through an oxidant, thereby increasing the mesopore ratio of porous carbon materials.
[0067] In the description of this specification, the references to terms such as "an embodiment," "some embodiments," "a method of implementation," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0068] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for preparing porous carbon materials, characterized in that, include: Phenolic monomers, aldehyde monomers, catalysts, surfactants, oxidants and water are mixed and the resulting raw material mixture is subjected to a first reaction to obtain a functionalized phenolic resin precursor. The functionalized phenolic resin precursor is mixed with an activator to carry out a second reaction, thereby obtaining a porous carbon intermediate. The porous carbon intermediate was acid-washed with acid to obtain a porous carbon material.
2. The preparation method according to claim 1, characterized in that, Includes at least one of the following conditions: The phenolic monomers include at least one of hydroquinone, catechol, resorcinol, and phenol; The aldehyde monomers include at least one of formaldehyde, furfural, vanillin, and acetaldehyde; The catalyst includes at least one of ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, triethylamine, diethylamine, dimethylethanolamine, ethylenediamine, and pyridine. The surfactant includes at least one of cetyltrimethylammonium bromide, polyethylene glycol, and polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer; The oxidant includes at least one of sodium perborate, potassium ferrate, and ammonium persulfate. The functional group includes at least one of carbonyl and ester groups.
3. The preparation method according to claim 1, characterized in that, Includes at least one of the following conditions: The mass ratio of the phenolic monomer, aldehyde monomer, catalyst, and surfactant is 1:(1.2~2.5):(0.06~0.1):(0.01~0.5). The mass ratio of the phenolic monomer to the oxidant is 1:(0.01~0.1). The amount of water used is 5% to 20% of the total mass of the solid raw materials in the raw material mixture; The temperature of the first reaction is 70℃~100℃, and the time is 2h~15h.
4. The preparation method according to claim 1, characterized in that, Prior to the second reaction, the preparation method further includes drying the functionalized phenolic resin precursor; preferably, the drying temperature is 70°C to 100°C.
5. The preparation method according to claim 1, characterized in that, Includes at least one of the following conditions: The activator includes at least one of KOH and NaOH; The mass ratio of the functionalized phenolic resin precursor to the activator is 1:(1.2~2.5). The second reaction is carried out at a temperature of 800℃~1300℃ for a time of 2h~15h; The atmosphere for the second reaction is an inert atmosphere; preferably, the inert atmosphere includes at least one of nitrogen or argon.
6. The preparation method according to claim 1, characterized in that, Includes at least one of the following conditions: The acid solution includes at least one of hydrochloric acid, sulfuric acid, and nitric acid; The mass ratio of the acid solution to the porous carbon intermediate is 1:(0.5~1.5).
7. The preparation method according to claim 1, characterized in that, After pickling, the preparation method further includes post-treatment of the pickled product; preferably, the post-treatment includes: dispersing the pickled product in water, washing, and drying.
8. The preparation method according to claim 7, characterized in that, Includes at least one of the following conditions: The dispersion period is 1 to 2 days; The washing includes vacuum filtration washing; The washing is performed 3 to 5 times; The drying includes vacuum drying; The drying temperature is 70℃~100℃.
9. A porous carbon material prepared by the preparation method according to any one of claims 1 to 8.
10. The porous carbon material according to claim 9, characterized in that, The mesopore content of the porous carbon material is 18% to 30%.